2004
DOI: 10.1016/s0002-9440(10)63784-4
|View full text |Cite
|
Sign up to set email alerts
|

Male Infertility and DNA Damage in Doppel Knockout and Prion Protein/Doppel Double-Knockout Mice

Abstract: The prion protein (PrP) and Doppel (Dpl) have many structural and biochemical properties in common, leading to the suggestion that the lack of an obvious phenotype in PrP-deficient mice maybe because of compensation by Dpl. To test this hypothesis and also investigate the function of Dpl we have generated Prnd ؊/؊ and Prnp ؊/؊ /Prnd ؊/؊ mouse lines. Both develop normally and display an identical male sterility phenotype that differs from that reported for another Prnd ؊/؊ mouse line. Sperm from both our mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 47 publications
2
55
1
2
Order By: Relevance
“…It is worth mentioning that the unusual glycoforms found in astrocytoma-derived cell lines were also detected in astrocytoma brain homogenates (Chiarelli, personal communication), strengthening the suggestion that changes in glycosylation are often one of the hallmarks that accompany malignant transformations (41). The doppel protein isolated from astrocytoma-derived cell lines exhibited a cytoplasmic cellular localization, different from that expected for GPIanchored membrane signal, as revealed in immunohistochemical staining of the Sertoli cells performed on sections of normal and pathological testes from human (10,11), mouse (42) and cattle (43). Besides, the reported Dpl-EGFP expression comparison experiments in astrocytoma and in HeLa cells demonstrated that a different tumor cell environment could justify per se the membrane or cytoplasmic sorting of the Dpl protein.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It is worth mentioning that the unusual glycoforms found in astrocytoma-derived cell lines were also detected in astrocytoma brain homogenates (Chiarelli, personal communication), strengthening the suggestion that changes in glycosylation are often one of the hallmarks that accompany malignant transformations (41). The doppel protein isolated from astrocytoma-derived cell lines exhibited a cytoplasmic cellular localization, different from that expected for GPIanchored membrane signal, as revealed in immunohistochemical staining of the Sertoli cells performed on sections of normal and pathological testes from human (10,11), mouse (42) and cattle (43). Besides, the reported Dpl-EGFP expression comparison experiments in astrocytoma and in HeLa cells demonstrated that a different tumor cell environment could justify per se the membrane or cytoplasmic sorting of the Dpl protein.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, whereas prion protein (PrP) is widely expressed, showing the highest expression profiles within the CNS (6), doppel shows barely detectable levels in most tissue (4,7). Doppel protein (Dpl) was found highly expressed only in adult and fetal testis (8), and different groups recently proposed an involvement in male gametogenesis (9)(10)(11). Based on the structural similarities between PrP (12) and Dpl (13), a role of doppel in the development of prion neurodegenerative diseases was hypothesised (14).…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, our observation is consistent with a role of Doppel in gonad differentiation in ruminants. This hypothetical newly identified function, apparently different from that of Doppel in mice (Behrens et al, 2002;Paisley et al, 2004), remains to be experimentally validated.…”
Section: Cellular and Subcellular Localization Of Doppel Protein In Gmentioning
confidence: 92%
“…Similarly, recent immunohistochemical studies performed in human, mouse, rat, boar, ovine, and bovine reproductive tracts revealed both developmental and spatial differences in Doppel expression profiles (Peoc'h et al, 2002;Rondena et al, 2005;Uboldi et al, 2005;Espenes et al, 2006;Serres et al, 2006). Prnd knockout in mice re-sulted in male sterility associated with a sperm inability to perform the acrosome reaction and with elevated levels of oxidative DNA damage (Behrens et al, 2002;Paisley et al, 2004). It was also observed that, in the absence of PrP, ectopic expression of Doppel induced the degeneration of Purkinje cells (Mo et al, 2001;Rossi et al, 2001;Anderson et al, 2004;Al Bersaoui et al, 2005).…”
Section: Introductionmentioning
confidence: 89%
“…STI1, whose interaction with PrP C mediates neuroprotection through a cAMP/PKA signaling pathway [114] could be the receptor. Moreover, endogenous PrP has been found to protect cultured neurons against oxidative stress, and brain tissue against ischemia, hypoxia, or trauma in vivo [75,97]. Nevertheless, how the putative neuroprotective activity of PrP C might be altered during prion diseases to produce a neurotoxic effect remains unknown.…”
Section: Participation Of Prpmentioning
confidence: 99%